Faktor - Faktor yang Mempengaruhi Bounding Attachment Masa Nifas - Dewi Susilawati; Nur Fadjri Nilakesuma; Risnawati Risnawati (Jurnal Keperawatan Silampari, 2020)
The purpose of this study was to determine the factors that affect puerperal breastfeeding attachment. The research method used was descriptive-analytic research with a cross-sectional design. The study results describe the variables of maternal characteristics (age, education, and parity) that affect the bounding attachment, with only parity variables with p values of 0.041. In addition, the effect on bounding attachment is the parent / family response variable (p = 0.036) and social support (p = 0.029) while there is no influence of the level of knowledge with bounding attachment (p = 1,000). In conclusion, socialize bounding attachment to mothers, families, the community to increase mother's knowledge and increase the success of Bounding Attachments between mother and child. Keywords: Bounding Attachment, Postpartum Mother, Postpartum Bonding Questionnaire (PBQ)